Evolutionary Interpretation of International Treaties - الحياني فتحي محمد (Journal of Legal Sciences, 2020)
This article dealt with the evolutionary interpretation in three parts: First, it focused on the conceptual framework of evolutionary interpretation of International Treaties, its philosophical and legal foundation and its determinants. As for the second topic, it dealt with the position of the International Court of Justice from the evolutionary interpretation, studying and analyzing its precedents in this aspect and the resulting proposed and adopted criteria. The third topic dealt with the position of the judiciary of human rights through analyzing the rulings of the European Court of Human Rights and the Inter - American Court of Human Rights based on the criteria that were produced by the judicial practices, which varied according to the type of treaty and its temporal extent, the nature of the term, the trend adopted in international law in addition to other criteria that are related The method of interpretation is the same as that associated with the independent meaning or the effective method of interpretation.